2006
DOI: 10.1116/1.2216722
|View full text |Cite
|
Sign up to set email alerts
|

Large reduction of leakage currents in AlGaN Schottky diodes by a surface control process and its mechanism

Abstract: Leakage currents in AlGaN Schottky diodes were investigated systematically by using a rigorous computer simulation based on the thin surface barrier model taking account of unintentionally doped surface donors. The leakage currents in AlGaN Schottky diodes have stronger bias dependence and smaller temperature dependences as compared with those of GaN diodes. It was shown that these features were associated with shallow oxygen donors located near the AlGaN surface. Then, an attempt was made to remove oxygen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Before applying the surface control process, leakage currents in the Pd Schottky diode were very large, about 10 −3 -10 −4 A/cm 2 at a reverse bias of −1.5 V. Current changes caused by hydrogen exposure in such diodes were very small, 2 one order of magnitude at most at exposure to 10 Torr hydrogen. On the other hand, by applying the surface control process, reverse current densities of the diode were reduced by three to four orders of magnitude down to about 10 −7 A/cm 2 at a reverse bias of −1.5 V. Thus, the surface control process is not only effective for Au/ Ni Schottky diodes as reported previously, 10 but also for Pd Schottky diodes. This effect not only increased the hydrogen sensitivity of the diode, but also made a detailed analysis of the I-V and C-V characteristics as presented here possible.…”
Section: A Effect Of Surface Control Process On I-v Characteristics mentioning
confidence: 50%
See 2 more Smart Citations
“…Before applying the surface control process, leakage currents in the Pd Schottky diode were very large, about 10 −3 -10 −4 A/cm 2 at a reverse bias of −1.5 V. Current changes caused by hydrogen exposure in such diodes were very small, 2 one order of magnitude at most at exposure to 10 Torr hydrogen. On the other hand, by applying the surface control process, reverse current densities of the diode were reduced by three to four orders of magnitude down to about 10 −7 A/cm 2 at a reverse bias of −1.5 V. Thus, the surface control process is not only effective for Au/ Ni Schottky diodes as reported previously, 10 but also for Pd Schottky diodes. This effect not only increased the hydrogen sensitivity of the diode, but also made a detailed analysis of the I-V and C-V characteristics as presented here possible.…”
Section: A Effect Of Surface Control Process On I-v Characteristics mentioning
confidence: 50%
“…In order to remove oxygen from the AlGaN layer, a surface control process, which we recently proposed, 10 was applied before Pd deposition. As shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A good agreement between these SBH values indicated that the Ni/AlGaN structure had good interface quality without an additional interfacial layer such as an oxide layer. Although relatively high leakage currents flow at the reverse bias region, 12,13 as shown in Fig. 1͑a͒, an excellent linearity of 1 / C 2 -V plots is obtained in the given reverse bias range.…”
mentioning
confidence: 88%
“…A GaN layer after growth naturally contains many defects near the surface. 3,9,44 These defects tend to generate electronic surface levels that capture carriers, resulting in nonradiative recombination and degradation of the light emitting efficiency. Through oxidation, these defects could have been consumed into the oxide layer: namely, defects near the surface could be reduced by oxidation.…”
Section: Surface Passivation Effectsmentioning
confidence: 99%